Plants in vitro propagation with its applications in food, pharmaceuticals and cosmetic industries; current scenario and future approaches - Hasnain, Ammarah; Naqvi, Syed Atif Hasan; Ayesha, Syeda Iqra; Khalid, Fatima; Ellahi, Manahil; Iqbal, Shehzad; Hassan, Muhammad Zeeshan; Abbas, Aqleem; Adamski, Robert; Markowska, Dorota; Baazeem, Alaa; Mustafa, Ghulam; et al. (Frontiers in Plant Science, 2022)
Plant tissue culture technique employed for the identification and isolation of bioactive phytocompounds has numerous industrial applications. It provides potential benefits for different industries which include food, pharmaceutical and cosmetics industries. Various agronomic crops i.e.,, cereals, fruits, vegetables, ornamental plants, and forest trees are currently being used for in vitro propagation. Plant tissue culture, coupled with biotechnological approaches, leads towards a sustainable agricultural development providing solutions to major food security issues. Plants are the rich source of phytochemicals with medicinal properties rendering them useful for the industrial production of pharmaceuticals and nutraceuticals. Furthermore, there are numerous plant compounds with application in the cosmetics industry. In addition to having moisturizing, anti‐ageing, anti‐wrinkle effects; plant-derived compounds also possess pharmacological properties such as antiviral, antimicrobial, antifungal, anticancer, antioxidant, anti-inflammatory, and anti-allergy characteristics. The in vitro propagation of industrially significant flora is gaining attention because of its several advantages over conventional plant propagation methods. One of the major advantages of this technique is the quick availability of food throughout the year, irrespective of the growing season, thus opening new opportunities to the producers and farmers. The sterile or endangered flora can also be conserved by plant micro propagation methods. Hence, plant tissue culture is an extremely efficient and cost-effective technique for biosynthetic studies and bio-production, biotransformation, or bioconversion of plant-derived compounds. However, there are certain limitations of in-vitro plant regeneration system including difficulties with continuous operation, product removal, and aseptic conditions. For sustainable industrial applications of in-vitro regenerated plants on a large scale, these constraints need to be addressed in future studies.